Cultured Meat, An Alternative for Conventional Meat - Gabriel POPESCU; Dorin MARTIN; Maria GIRIP (Communications of International Proceedings, 2021)
Lately, the increase in the number of inhabitants of the planet has generated a greater demand for food and more specific products based on animal proteins, which has led to many debates regarding the livestock sector and meat consumption. All these debates refer to the environmental problems caused by animal farms and the advantages of artificial meat production; there is a growing demand and support for this type of meat, created in the laboratory, from several opinion leaders from outside the farming community. This type of meat is presented as a real solution to our environmental challenges and the growing demand for meat on the market. Artificial meat production is now increasingly promoted by leading technology leaders, who are making strong statements in favor of artificial meat with substantial investment in this sector. This vision of high technologies for meat production, which is receiving more and more attention in recent years, is very little explained and analyzed without knowing all the social, environmental, economic, and public health effects. The claim that a diet without "real meat" and a Europe without animal husbandry are the answers to the challenges posed by climate change is incorrect. It could lead to a catastrophe for our nutrition, territories, environment, diversity, and culture.
Keywords: Artificial Meat; Livestock; Sustainability.